Program Evaluation of A Community-Based Drug Rehabilitation Center: The Perspectives of The Persons Who Use Drugs (PWUDs) - Argel Bondoc Masanda; Gino Cabrera; Alain Bernard Andal; Clarissa Delariarte; Gil Jeff Tanganco; Alyanna Fae Balbuena (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
Bahay Pagbabago ni Apong Pilar is a community-based, church-initiated, and DDB (Dangerous Drugs Board) recognized and accredited formation shelter in San Simon, Pampanga. Using the sequential explanatory design, this study conducted surveys and focused-group discussions with 32 reformists to assess the shelter's formation program based on the reformists' standpoints. Quantitative results using Spearman's rank correlations showed that there seemed to be a significant relationship between attitude towards livelihood (ρ (2) = 6.589, sig. = 0.037*, p < 0.05) and spiritual activities (ρ (27) = 0.587**, p < 0.01), as formative components of the program, and perceived self-improvement (ρ (2) = 13.573, sig. = 0.001**, p < 0.01) during their stay in the formation shelter. It suggests that as the reformist develops a more positive attitude towards the livelihood, sports, and spiritual activities being offered at the formation center, it is also more likely that they may develop a higher sense of self-improvement. Qualitative data yielded three general themes: (1) finding a higher purpose and deeper meaning in life through spiritually uplifting undertakings; (2) having family-oriented treatment, making them feel nothing less of their humanity; and (3) having holistic and dynamic activities, those that focus on the developmental facets. These are the elements deemed by the reformists as important, which constitute effective reintegration to their families, communities, and society.